The right to the smart city - Cardullo, Paolo; Di Felicaiantonio, Cesare; Kitchin, Rob (Emerald Publishing, 2019)
Globally, Smart Cities initiatives are pursued which reproduce the interests of capital and neoliberal government, rather than wider public good. This book explores smart urbanism and 'the right to the city', examining citizenship, social justice, commoning, civic participation, and co-creation to imagine a different kind of Smart City.